Knowledge, attitude and practice among private medical professionals enrolled in public private partnership program for prevention of mother to child transmission of human immunodeficiency virus in three districts of Karnataka - H. Jagadish, Deepak Murthy; Gudegowda, Kishore Shettihalli; Sobagaiah, Ranganath T.; Neela, Vishwanatha V. (International Journal Of Community Medicine And Public Health, 2019)
Background: Human immunodeficiency virus (HIV), the virus that causes acquired immunodeficiency syndrome (AIDS), is one of the world’s most serious public health challenges. Nearly all young children newly infected with HIV are infected through mother-to-child transmission. Only about half of the HIV infected mothers received ART and quarter of the babies born through HIV infected mothers receive ARV prophylaxis. This low coverage due to a high proportion of women delivering in private health facilities. Lack of policy for the private sector, inadequate knowledge and fear of occupational exposure are some barriers. Methods: A cross sectional study conducted among private practitioners enrolled in parent to child transmission (PPTCT) program in three districts of Karnataka. 175 obstetricians and pediatricians engaged in giving care to HIV infected mother and children were selected randomly and were interviewed using a pre tested semi structured questionnaire and the scores were graded. Results: Mean age of the participants was 38.95 years with SD of 9.12 years. The mean years of experience was found to be 14.36 years with SD of 6.45 years. The knowledge was average scoring 66.56%. The attitude and practice were 69.21% and 64.21% respectively. The mean score for KAP was 28.89 (9.56) out of 43 questions. There was significant association between age of the participants, specialization and years of experience with scoring. Conclusions: The knowledge, attitude and practice among private practitioners were average. To enhance the coverage of PMTCT, there is a need for strengthening private sector with strong political will thus reducing morbidity and mortality of the disease.